Von Willebrand Factor Multimer Analysis and Classification: A Comprehensive Review and Updates - Saadalla, Abdulrahman; Seheult, Jansen; Pruthi, Rajiv K.; Chen, Dong (Seminars in Thrombosis and Hemostasis, 2022)
Von Willebrand factor (VWF) is a multimeric glycoprotein with essential roles in primary hemostasis. Patients with von Willebrand disease (VWD), due to quantitative and/or qualitative defects of VWF usually experience mucocutaneous bleeding. Based on the laboratory results of VWF antigen, various VWF activities, factor VIII activity, and VWF multimer patterns, VWD can be categorized as type 1, 2, and 3 VWD. VWF multimer analysis by either manual or semi-automated electrophoresis and immunoblotting is a critical part of the laboratory testing to differentiate type 1, type 2 VWD, and subtypes of type 1 or 2 VWD. The multimer distribution patterns can also help to understand the underlying molecular mechanism of VWF synthesis, multimerization, and clearance defects in VWD. This review will cover VWF synthesis, multimerization, secretion, VWF multimer analysis, and VWF multimer interpretation of various types and subtypes of VWD.
Keywords: von Willebrand factor; von Willebrand disease; multimer